2017
DOI: 10.1002/nav.21763
|View full text |Cite
|
Sign up to set email alerts
|

Optimal maintenance policies for a safety‐critical system and its deteriorating sensor

Abstract: We consider the integrated problem of optimally maintaining an imperfect, deteriorating sensor and the safety‐critical system it monitors. The sensor's costless observations of the binary state of the system become less informative over time. A costly full inspection may be conducted to perfectly discern the state of the system, after which the system is replaced if it is in the out‐of‐control state. In addition, a full inspection provides the opportunity to replace the sensor. We formulate the problem of adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Lovejoy (1987) obtained monotonicity results for informativeness in a partial information environment, providing insights into when one observation set is more informative than another. The informativeness of the sensor observations are further motivated by Lévesque & Maillart (2008) and Van Oosterom et al (2017). In their work, Lévesque & Maillart (2008) investigated the effect of costly, partial information observations (not by means of sensors) of varying informativeness on the assessment of business opportunities, such as diamond mining.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lovejoy (1987) obtained monotonicity results for informativeness in a partial information environment, providing insights into when one observation set is more informative than another. The informativeness of the sensor observations are further motivated by Lévesque & Maillart (2008) and Van Oosterom et al (2017). In their work, Lévesque & Maillart (2008) investigated the effect of costly, partial information observations (not by means of sensors) of varying informativeness on the assessment of business opportunities, such as diamond mining.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors showed that the optimal policy consists of a pair of threshold values governing the acceptance or rejection of such an opportunity. Decreasing sensor informativeness over time was investigated by Van Oosterom et al (2017). The authors jointly optimized and analyzed the maintenance of a system and its deteriorating sensor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impacts of maintenance to performances have been extensively studied in past decades 10-13 . From the energy retrofitting perspective, maintenance actions can restore the energy savings via reversing the population decay, that is, restoring a number of failed devices to normal working condition.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of VoI analysis to Structural Health Monitoring are presented by Pozzi and Der Kiurehian, Straub, Schweckendiek and Vrouwenvelder, Qin et al, and Zonta et al Evaluation of VoI in sequential infrastructure management is illustrated by Srinivasan and Parlikad . The recent interest in evaluating the economic impact of integrating sensors in infrastructure management is testified by many researches . Assessing the VoI allows for an appropriate calibration of investments in inspections, sensors, and monitoring systems, as the overall investment for collecting information should not exceed its value, In addition, it allows for comparing expensive explorative actions (as installing monitoring systems) with “exploitative” actions (i.e., actions that change the actual condition of the system, as retrofitting a component) on an equal ground.…”
Section: Introductionmentioning
confidence: 99%
“…9 The recent interest in evaluating the economic impact of integrating sensors in infrastructure management is testified by many researches. [10][11][12][13][14] Assessing the VoI allows for an appropriate calibration of investments in inspections, sensors, and monitoring systems, as the overall investment for collecting information should not exceed its value, In addition, it allows for comparing expensive explorative actions (as installing monitoring systems) with "exploitative" actions (i.e., actions that change the actual condition of the system, as retrofitting a component) on an equal ground.…”
Section: Introductionmentioning
confidence: 99%